Evaluasi Kinerja Operasional Pelayanan Bus Rapid Transit (B Koridor Blok M-Kota, DKI Jakarta - Clara Vidhia; Franka Hendra (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
The operational aspect as an aspect directly related to the provision of services to the community will certainly require this BRT system to provide better service quality compared to other public transport service systems. The objectives of this research are: to assess the operational performance of BRT services in DKI Jakarta in the Blok M-Kota corridor in terms of headway, load factor and travel time based on BRT service performance standards and to assess public perceptions of the operational performance of BRT services in corridors. Blok M-City. In this study using descriptive analysis methods, evaluative, and science methods. The survey technique was carried out by means of a static survey, on bus, interviews, and questionnaires. The results showed that the headway, BRT has a good level of service, when compared to the standard of the Directorate General of Land Transportation where the average standard headway is 5 minutes. While the standard of BP TransJakarta can be said to be good where the headway during peak hours is 2-3 minutes and non-peak hours are 5 minutes. Load factor, the results of the primary survey and analysis show that the load factor has not yet reached the operational target of BP TransJakarta by 70% so that the bus condition still feels roomy and relaxed, although it is much better according to the standards of the Directorate General of Land Transportation. As for travel time, the operational service performance of BRT is in accordance with the standards of the Directorate General of Land Transportation which stipulates the standard travel time is 1-1.5 hours and BP TransJakarta sets 45 minutes, which is much faster where for the Blok M-Kota and Kota-Blok majors. M.